Keefektifan Pelaksanaan Bimbingan di Sekolah Dasar Negeri - M. Fatchurachman (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2005)
The purpose of the study is to know the effectiveness of guidance at Public Primary Schools in Palangka Raya. The subject of the study was 114 teachers of State Primary Schools. The method of study is descriptive study. Data collection used questionnaires. The collected data was analyzed by using percentages. The result concluded that the guiding activity of the teachers of Public Primary school can be categorized as effective.